2021
DOI: 10.1071/fp21165
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of

Abstract: Soil salinity is a significant threat to sustainable agricultural production. Plants must adjust their developmental and physiological processes to deal with environmental salt conditions. We previously identified 18 serine-arginine-rich (SR) proteins from cassava (Manihot esculenta Crantz) that play pivotal roles in alternative splicing when encountering the external stress condition. However, functional characterisation of SR proteins is less reported in cassava, which is an important staple crop in the worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In fact, previous phenotypic studies of adult Arabidopsis plants from single mutants in individual SCL genes did not report any visible alterations, with only a quintuple mutant of the four SCL members and the SC35 gene ( scl28 scl30 scl30a scl33 sc35 ) exhibiting clear defects in leaf development and flowering (Yan et al, 2017). In a recent report, heterologous overexpression of the cassava ( Manihot esculenta ) MeSCL30a gene in Arabidopsis plants is described as increasing salt stress sensitivity during seed germination (Hu et al, 2021). However, MeSCL30a also shares high identity with the Arabidopsis SCL33 protein and was expressed at extremely high levels in Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous phenotypic studies of adult Arabidopsis plants from single mutants in individual SCL genes did not report any visible alterations, with only a quintuple mutant of the four SCL members and the SC35 gene ( scl28 scl30 scl30a scl33 sc35 ) exhibiting clear defects in leaf development and flowering (Yan et al, 2017). In a recent report, heterologous overexpression of the cassava ( Manihot esculenta ) MeSCL30a gene in Arabidopsis plants is described as increasing salt stress sensitivity during seed germination (Hu et al, 2021). However, MeSCL30a also shares high identity with the Arabidopsis SCL33 protein and was expressed at extremely high levels in Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…It was known that the modulation of SR gene isoforms by salt might destabilize the spliceosome complex to accurately recognize the splice sites ( Albaqami et al, 2019 ; Laloum et al, 2021 ). Our previous studies showed that salt stress promotes the alternative 5′ and 3′ splice-site selection and IR events which led to introduce premature termination (nonsense) codons (PTCs) in the pre-mRNA of SR proteins ( Ding et al, 2014 ; Gu et al, 2020 ; Hu et al, 2021 ). Consistent with these studies, several SR proteins were abnormally spliced under high salinity in date palm ( Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…FIERY2/CTD phosphatase-like 1 (FRY2/CPL1) interacted with AtRS40 and AtRS41 proteins, and the loss-of-function mutations showed the hypersensitive phenotype in response to salt and ABA ( Chen et al, 2013 ). Ectopic overexpression of cassava SCL30A and SR34 proteins could improve the salt tolerance in plants ( Gu et al, 2020 ; Hu et al, 2021 ). Therefore, extensive analysis of SR proteins would provide novel insights on their essential role for proper gene expression underlying salt stress in date palms.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that the splicing of stress-responsive genes and spliceosome components can be altered by salt stress, which influences the salt tolerance of plants by adjusting the homeostasis of ROS and osmosis. For example, serine/arginine-rich (SR)-like protein, as a component of spliceosome, have been reported to negatively regulate salt stress [ 53 , 54 ]. Among the twelve serine/arginine-rich splicing factors among the selected DEGs in this study, nine genes ( BnaA03g00590D , BnaA06g21030D , BnaA07g06170D , BnaC02g27300D , BnaC07g07660D , BnaC08g16960D , BnaC08g38300D , BnaCnng19170D , Brassica_napus_newGene_614 ) were from the set “down-R. in T.” ( Table S6 ).…”
Section: Discussionmentioning
confidence: 99%